ADVANCED DENTAL CEMENTATION: A FOCUS ON ESTHETICS - Turcu Gabriela; Oana Cucoveica; Alina Stefanache; Codrin Paul Fuioaga; Cosimo Caltabellotta; Norin Forna; Carmen Stadoleanu; Radu Mircea Sireteanu-Cucui (Romanian Society of Oral Rehabilitation, 2024)
Aim of the Study: The aim of this study is to provide a comprehensive analysis of dental cementation techniques, focusing on the advantages and disadvantages of various approaches, as well as their impact on esthetics in restorative dentistry. Material and Methods: This study employed a systematic approach to gather relevant information, conducting extensive research using electronic databases such as PubMed, Google Scholar, and Web of Science. Articles released from April onwards were targeted, focusing exclusively on English-language publications. A comprehensive set of keywords, including "dental cementation," "advantages," "disadvantages," and "esthetic outcomes," were utilized to ensure thorough coverage of the topic. Results: The analysis of dental cementation techniques revealed a range of advantages and disadvantages associated with different approaches. These findings provide valuable insights into the impact of various cementation methods on esthetic outcomes in restorative dentistry. Dental cements are engineered to secure restorations, appliances, and post-and-core systems in a stable and durable manner within the oral environment. Conventional glass ionomer and zinc phosphate cements are among the most widely used materials for luting metallic restorations and posts. In contrast, resin-based cements are favored for esthetic applications. The successful cementation of esthetic restorations largely depends on the proper treatment and silane application to the internal surface of the restoration. Conclusions: The findings of this study highlight the importance of carefully considering the advantages and disadvantages of dental cementation techniques in restorative dentistry. Understanding the impact of these methods on esthetic outcomes is crucial for optimizing patient care and treatment outcomes. Further research in this area is warranted to continue improving dental cementation practices and enhancing esthetic results for patients.